Two new species of genus \(Helicteres\) (Helicteroideae, Malvaceae) from Vietnam - Dang, Van Son; Truong, Ba Vuong; Hoang, Nghia Son; Nguyen, Van Tu; Nguyen, Quoc Bao; Pham, Quoc Trong; Le, Van Tho; Kieu, Cam Nhung; Bui, Van Huong; Naiki, Akiyo (Academia Journal of Biology, 2022)
Two new species of genus Helicteres (Malvaceae, Helicteroideae), Helicteres Taynguyenenis and Helicteres dakmilensis from the Central Highlands of Vietnam are described and illustrated. H. taynguyenensis is morphologically similar to Helicteres angustifolia widely distributed in mainland SE Asia to China, Japan and Australia, but differs from the latter by having shorter petioles, larger calyx and petals, and longer androgynophores. Helicteres dakmilensis is closely related to Helicteres poilanei endemic to Vietnam, but distinguished by shorter petioles, fewer secondary veins, persistent stipules and bracts, larger calyx and fruits. The IUCN conservation status, vernacular name, illustrations, photographs, and comparison with the closest allies are provided for each of the new species.